Novel axe‐shaped circular microstrip quad band antenna. Issue 2 (February 2016) - Nafiza, N.; Sreeja, B. S.; Devi, R. Chithra; Radha, S.
ABSTRACT: Novel axe‐shaped circular microstrip quad band cost effective antenna with simple structure is developed. This design consists of circular patch with elliptical and circular slots loading provide an axe shape patch along with stubs offer quad bands. The proposed antenna provides resonance at the frequencies of 2.8, 4, 5.4, and 6.2 GHz which covers the applications of WLAN/WI‐FI and WIMAX. The measured results of reflection coefficient and VSWR are presented. The proposed design provides minimum rejection ratio of 23 dB and maximum rejection ratio of 15 dB. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:400–402, 2016